(untitled) (Research, Society and Development, 2021)
This article aims to establish a reflection on the dilemmas and impasses for the approximation between the public university and the public school, from a critical perspective of the current reality, in the sense of an insertion of students from the lower classes in education superior public, free and of quality. The project results justify the university’s ethical need for inclusion and democratization of higher education. With high school students as centrality, the main results are: i) the current feeling of estrangement in the face of the University; ii) the concern with student inclusion and permanence; iii) the understanding that access to the University is not a challenge or acceptance, but a right.